Keberfungsian Keluarga Bagi Penyesuain Sosial Mahasiswa Baru - Rofika Dewi Maulina; Sofa Amalia (JURNAL PSIKOLOGI, 2019)
Social adjustment is needed by new students when entering college so that they can adjust to the new environment in which they are studying.  One of the factors that can influence social adjustment is family functions. The aim of this study was to determine the effect of family functioning on social adjustment in new collage students. This study used a correlation research design with a sampling technique that is simple random sampling, with the subjects of the 268 new collage student aged 17-21 years. The instrument in this study uses the scale of The McMaster Family Assessment Device (FAD) and social adjustment subscale of The Student Adaptation to College Questionnaire (SACQ-SA). Data analysis using simple linear regression test. The outcome showed that there was an influence of family functioning on social adjustment in new collage students. The regression coefficient (r) is 0.301 with a value of p = 0,000 <0.05. It shows that the higher the family functioning, the higher the social adjustment of new students in college.